Measurement of vapor-liquid equilibria for the binary mixture of propylene (R-1270)+propane (R-290) - Ho, Quang Nhu; Yoo, Kye Sang; Lee, Byung Gwon; Lim, Jong Sung (ELSEVIER SCIENCE BV, 2006)
Isothermal vapor-liquid equilibria data for the binary mixture of propylene (R-1270) + propane (R-290) at 273.15, 278.15, 283.15, 293.15, 303.15 and 313.15 K were measured by using a circulation-type equilibrium apparatus. The experimental data were correlated with the Peng-Robinson equation of state (PR-EOS) combined with the Wong-Sandler mixing rule. It is confirmed that the data calculated by this equations of state are in good agreement with experimental data. The azeotropic behavior was not found in this mixture over range of temperature studied here. (c) 2006 Published by Elsevier B.V.
Keywords: MIXING RULE; STATE; VOLATILITY; EQUATION